PROMOTING TOTAL PHYSICAL RESPONSE (TPR) METHOD ON EARLY CHILDHOOD ENGLISH LANGUAGE TEACHING - Cicih Nuraeni (Jurnal Penelitian Humaniora, 2019)
The purpose of this study was to describe the use of Total Physical Response (TPR) method on early childhood English Language Teaching (ELT) at Panti Asuhan Yauma Jakarta and to know the students’ response after learning English using TPR method. The method of the research is descriptive qualitative. In this research the researcher describes the activities carried out by teachers and students by using TPR method. The data resources are from teacher and students in Panti Asuhan Yauma Jakarta . The class consist of 6 students which their age was around  5 to 11 years old. The data collected through observation and interview both teacher and students. The instruments were pre-test and post-test with 2 (two) criterion being assessed, namely vocabulary and comprehension. They were divided into 6 (six) elements such as accuracy of word, understanding each word, word choice, understanding the meaning, speaking easily,and intonation. The results showed that there was any improvement on vocabulary score about 26.16 and comprehension score about 27.16. The research finding firstly showed the TPR method was able to be applied to children because they enjoyed and were also very active in learning English. The researcher hopes that the study contributes to the activities of teaching and learning English, especially teaching English for early childhood. It was proved by the score from pre-test and post-test.